2018
DOI: 10.3390/nano8050351
|View full text |Cite
|
Sign up to set email alerts
|

Electrically Guided DNA Immobilization and Multiplexed DNA Detection with Nanoporous Gold Electrodes

Abstract: Molecular diagnostics have significantly advanced the early detection of diseases, where the electrochemical sensing of biomarkers (e.g., DNA, RNA, proteins) using multiple electrode arrays (MEAs) has shown considerable promise. Nanostructuring the electrode surface results in higher surface coverage of capture probes and more favorable orientation, as well as transport phenomena unique to nanoscale, ultimately leading to enhanced sensor performance. The central goal of this study is to investigate the influen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 45 publications
(69 reference statements)
0
19
0
Order By: Relevance
“…Veselinovic et al further demonstrated that nanostructuring the surface of electrodes leads to higher surface coverage and consequently enhanced sensor performance. Specifically, they integrated nanoporous gold multielectrode arrays within microchannels for facilitating the multiplexed detection of DNA biomarkers for cancer, namely the BRCA1, BRCA2, and p53 breast cancer-related genes, through electrophoretic guidance [ 83 ]. Similarly, Wu et al developed an amplification-free, SERS microfluidic approach for the detection of KRAS gene, commonly known for its mutations in cancer cells [ 84 ].…”
Section: Diagnostic Applicationsmentioning
confidence: 99%
“…Veselinovic et al further demonstrated that nanostructuring the surface of electrodes leads to higher surface coverage and consequently enhanced sensor performance. Specifically, they integrated nanoporous gold multielectrode arrays within microchannels for facilitating the multiplexed detection of DNA biomarkers for cancer, namely the BRCA1, BRCA2, and p53 breast cancer-related genes, through electrophoretic guidance [ 83 ]. Similarly, Wu et al developed an amplification-free, SERS microfluidic approach for the detection of KRAS gene, commonly known for its mutations in cancer cells [ 84 ].…”
Section: Diagnostic Applicationsmentioning
confidence: 99%
“…For example, in the development of a multiplexed sensor for breast cancer genes. [130] Nanoporous noble metals have been employed in many other biomedical fields. Nanoporous materials with a platinum-gold alloy have been used for glucose sensing.…”
Section: Porous Metal Materialsmentioning
confidence: 99%
“… developed a rapid and sensitive assay in a microfluidic device based on a multivalent aptasensor array chip and silver aggregated amplification for detection of proteins platelet‐derived growth factor‐BB and vascular endothelial growth factor‐165 by fluorescence. The multiplexed detection of three different biomarker genes relevant to a breast cancer diagnosis was performed by Veselinovic and co‐workers through square wave voltammetry. They used electrically guided immobilization of DNA probes for nucleic acid in a multiplexed format.…”
Section: Introductionmentioning
confidence: 99%